Guyana : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The aim is to analyze the main channels of transmission for shocks from the global economy to Guyana and assess their specific spillover magnitudes. The paper documents the transmission channels of external shocks to the real economy and the financial sector, citing magnitudes and risks. It then describes the policy response, including recent directions of monetary and fiscal policies to weather the spillover of external shocks on the domestic economy through the real and trade channel, and provides an outlook for the envisaged recovery of the global economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet